Drug policy: history, theory and consequences: examples from Denmark and USA - Frank, Vibeke Asmussen (Aarhus Univ. Press, 2008)
Drug policy has spread into new areas of society and new players are now engaged in this policy. This leads to the question: How can we understand and explain the increasingly complex puzzle that we call drug policy? A very wide range of drug policies are implemented in contemporary societies - not only by governments, but also by local communities, organisations, public institutions, private enterprises, sports clubs etc., with consequences for drug users, citizens and society in general. In Drug Policy anthropologists, criminologists and sociologists analyse different aspects of drug policy, seeing it as a way of regulation drugs - including control, treatment, prevention and harm reduction. Using examples from both Denmark and the USA, the authors' approach is to focus in particular on the history and consequences of drug policy in practice. The topic is analysed on an international, national as well as local level. This book will be of great value to advanced undergraduate and